2013
DOI: 10.1111/nph.12292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel microRNA (miRNA) from rice that targets an alternatively spliced transcript of the Nramp6 (Natural resistance‐associated macrophage protein 6) gene involved in pathogen resistance

Abstract: Plants have evolved efficient defence mechanisms to defend themselves from pathogen attack. Although many studies have focused on the transcriptional regulation of defence responses, less is known about the involvement of microRNAs (miRNAs) as post-transcriptional regulators of gene expression in plant immunity. This work investigates miRNAs that are regulated by elicitors from the blast fungus Magnaporthe oryzae in rice (Oryza sativa). Small RNA libraries were constructed from rice tissues and subjected to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
162
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(169 citation statements)
references
References 62 publications
7
162
0
Order By: Relevance
“…In powdery mildew disease of wheat caused by fungus Blumeria graminis f. sp.tritici (Bgt) have showed miRNA differential expression patterns-miR156, miR159, miR164, miR171 and miR396, were found to be down regulated while miR393, miR444 and miR827 were found to be up regulated [28]. Overexpression of Osa-miR7696 was found in rice blast infection [29].…”
Section: Fungal Infectionmentioning
confidence: 93%
“…In powdery mildew disease of wheat caused by fungus Blumeria graminis f. sp.tritici (Bgt) have showed miRNA differential expression patterns-miR156, miR159, miR164, miR171 and miR396, were found to be down regulated while miR393, miR444 and miR827 were found to be up regulated [28]. Overexpression of Osa-miR7696 was found in rice blast infection [29].…”
Section: Fungal Infectionmentioning
confidence: 93%
“…However, to date, limited studies imply that small RNAs may be involved in rice immunity against the blast fungus M. oryzae. A recent report assayed the accumulation of miRNAs in rice treated by elicitors extracted from blast fungal mycelia (Campo et al, 2013). A new rice miRNA, osa-miR7695, was identified to be involved in rice resistance by negatively regulating the transcript of NATURAL RESISTANCE-ASSOCIATED MACROPHAGE PROTEIN6 (Campo et al, 2013).…”
mentioning
confidence: 99%
“…A recent report assayed the accumulation of miRNAs in rice treated by elicitors extracted from blast fungal mycelia (Campo et al, 2013). A new rice miRNA, osa-miR7695, was identified to be involved in rice resistance by negatively regulating the transcript of NATURAL RESISTANCE-ASSOCIATED MACROPHAGE PROTEIN6 (Campo et al, 2013). Currently, miRBase lists over 700 mature miRNA sequences cloned or predicted in rice (http://www.mirbase.org; Kozomara and Griffiths-Jones, 2011).…”
mentioning
confidence: 99%
“…Sixth miR3979 gene family b stu-miR1030 (a to g): stu-miR1030a, stu-miR1030b, stu-miR1030c, stu-miR1030d, stu-miR1030e, stu-miR1030f and stu-miR1030g; stu-miR1510 (a and b): stu-miR1510a and stu-miR1510b; stu-miR2673 (a and b): stu-miR2673a and stumiR2673b. implicates to rice root development and resistance to the blast fungus Magnaporthe oryzae in rice (Campo et al, 2013). Importantly, seventh miR5021 family is called MYB transcription factor and is a key factor in regulatory networks controlling development, metabolism and responses to biotic and abiotic stresses (Dubos et al, 2010).…”
Section: Target Prediction Of Mirnas and Functional Analysismentioning
confidence: 99%
“…With the discovery of first miRNAs (lin-4 and let-7) in Caenorhabditis elegans (Olsen et al, 1999), in plants first miRNA was identified in Arabidopsis thaliana in 2002 (Park et al, 2002). Since then with the advent of modern computational tools and conserved nature of mature miRNAs, several miRNAs have been identified across the plant species such as potato (Xie et al, 2011;Yang et al, 2013;Zhang et al, 2013), Solanaceae plants (Kim et al, 2011), Arabidopsis (Liang et al, 2015), rice (Campo et al, 2013), wheat (Akdogan et al, 2015), Brassica juncea (Srivastava et al, 2013), chickpea (Kohli et al, 2014), citrus (Lu et al, 2014) and peach (Luo et al, 2013) to name a few. To date, a total of 24,521 distinct mature hairpin precursor miRNAs across 206 species have been annotated in the miRBase Release 20, an open online repository.…”
Section: Introductionmentioning
confidence: 99%